KOMPETENSI LULUSAN SEKOLAH MENENGAH KEJURUAN TEKNIKA KAPAL PENANGKAP IKAN (TKPI) YANG DIBUTUHKAN INDUSTRI - Sundoro, Achmad (2011)
This study raised the problems encountered by the writer at work, namely SMK Negeri 1 Kandanghaur where the learning process for productive subjects (SKKD) are constrained by the number of teachers that are not balanced by the number of students, plus the amount of productive subjects in great quantities. Since the competence of students fail to thrive, then when they graduate can't pass recruitment fishing vessels crew test, especially foreigners, it is proved by the reduced number of graduates entering ships from year to year. The graduates had difficulty because they can not compete with graduates from other schools. In order to overcome the problems faced, the authors made a direct approach to the places that can be used as a reference as a workplace for TKPI graduates to find information about the competencies that are considered more urgent to be learned in order to find a job when they graduate using qualitative research methods. Based on data from research, found ten SKKD from 25 SKKD deemed necessary further improved. Thus, even with all the limitations of school conditions including the number of teachers were minimal, the productive subjects content is delivered completely in accordance with the actual working conditions so that the students will be better prepared to compete to find work after graduation. However, due to the research sites is a location that is often in cooperation with the SMK Negeri 1 Kandangahur, so the results of this research is not appropriate for TKPI students from other schools. Therefore, the author recommend that teachers from other vocational high shcool conduct a similar study in accordance with the competency skills in order to get a vivid description of the competencies required by industry.